New 1,2,3-triazole linked ciprofloxacin-chalcones induce DNA damage by inhibiting human topoisomerase I& II and tubulin polymerization - Hamada H. H. Mohammed; Amer Ali Abd El-Hafeez; Kareem Ebeid; Aml I. Mekkawy; Mohammed A. S. Abourehab; Emad I. Wafa; Suhaila O. Alhaj-Suliman; Aliasger K. Salem; Pradipta Ghosh; Gamal El-Din A; Alaa M. Hayallah; Samar H. Abbas (Taylor & Francis Group, 2022)
A series of novel 1,2,3-triazole-linked ciprofloxacin-chalcones 4a-j were synthesised as potential anticancer agents. Hybrids 4a-j exhibited remarkable anti-proliferative activity against colon cancer cells. Compounds 4a-j displayed IC50s ranged from 2.53-8.67 µM, 8.67-62.47 µM, and 4.19-24.37 µM for HCT116, HT29, and Caco-2 cells; respectively, whereas the doxorubicin, showed IC50 values of 1.22, 0.88, and 4.15 µM. Compounds 4a, 4b, 4e, 4i, and 4j were the most potent against HCT116 with IC50 values of 3.57, 4.81, 4.32, 4.87, and 2.53 µM, respectively, compared to doxorubicin (IC50 = 1.22 µM). Also, hybrids 4a, 4b, 4e, 4i, and 4j exhibited remarkable inhibitory activities against topoisomerase I, II, and tubulin polymerisation. They increased the protein expression level of γH2AX, indicating DNA damage, and arrested HCT116 in G2/M phase, possibly through the ATR/CHK1/Cdc25C pathway. Thus, the novel ciprofloxacin hybrids could be exploited as potential leads for further investigation as novel anticancer medicines to fight colorectal carcinoma.